Implementasi Pasal 27 Peraturan Menteri Perhubungan Nomor PM 49 Tahun 2014 tentang Alat Pemberi Isyarat Lalu Lintas Perspektif Siyasah Tanfidziyah - Ajeng Gita Pitaloka; Agustina Nurhayati; Rizky Silvia Putri (Jurnal Hukum Lex Generalis, 2026)
Traffic and road transportation are systems consisting of various elements aimed at ensuring safety, order, and smooth traffic flow. Increased public mobility that is not balanced with infrastructure capacity causes congestion, especially at intersections that have the potential to cause conflict and accidents. One of the traffic control devices is the Traffic Signal Device (APILL) regulated in Article 27 of the Minister of Transportation Regulation Number PM 49 of 2014, which includes placement, maintenance and removal based on technical needs and evaluation of traffic conditions. This study aims to analyze the implementation of Article 27 in the Bandar Lampung City Transportation Agency and review it from the perspective of Siyasah Tanfidziyah. This study uses field research. The data used are primary and secondary data. Data collection techniques in this study are through observation, interviews and documentation. Data processing techniques are carried out through data reduction, data presentation and drawing conclusions. Data analysis used a qualitative method using analytical descriptive methods. The results of the study indicate that normatively the APILL policy is in accordance with applicable provisions, but in fact its implementation is not optimal. From the perspective of Siyasah Tanfidziyah, implementation has been in line with the principles of trust, justice, and public welfare, but has not been fully effective. Therefore, strengthening inter-agency coordination, increasing implementation effectiveness, and optimizing infrastructure management are necessary to enhance public safety and welfare.